Gender, source country characteristics and labor market assimilation among immigrants: 1980 - 2000 - Francine D. Blau; Lawrence M. Kahn; Kerry L. Papps (Institute for the Study of Labor (IZA), 2008)
We use 1980, 1990 and 2000 Census data to study the impact of source country characteristics on the labor supply assimilation profiles of married adult immigrant women and men. Women migrating from countries where women have high relative labor force participation rates work substantially more than women coming from countries with lower relative female labor supply rates, and this gap is roughly constant with time in the United States. These differences are substantial and hold up even when we control for wage offers and family formation decisions, as well as when we control for the emigration rate from the United States to the source country. Men's labor supply assimilation profiles are unaffected by source country female labor supply, a result that suggests that the female findings reflect notions of gender roles rather than overall work orientation. Findings for another indicator of traditional gender roles, source country fertility rates, are broadly similar, with substantial and persistent negative effects of source country fertility on the labor supply of female immigrants except when we control for presence of children, in which case the negative effects only become evident after ten years in the United States.
urn:nbn:de:101:1-20081014309
Keywords: D10; 330; Immigration; labor supply; fertility; assimilation; gender; Internationale Arbeitsmobilität; Einwanderung; Arbeitsmarkt; Integration; Männer; Frauen; USA; Internationale Arbeitsmobilität; Einwanderung; Arbeitsmarkt; Integration; Männer; Frauen; USA